KAJIAN KRITIS AKULTURASI ISLAM DAN BUDAYA LOKAL - Ibrahim, Nasruddin (Rihlah: Jurnal Sejarah dan Kebudayaan, 2021)
slam needs culture in order to spread its missions, both in the form of customs, traditions, art and so on. However, it is nfecessary to distinguish which Islam is a religion of monotheism which is universal, absolute and eternal and which is relative and temporal as part of human creation and at the same time as an expression of Islam. Cultural da’wah is nothing but an effort to carry out dynamism and purification. Dynamics means cultural creations that have a tendency to always develop and change for a better and more Islamic direction. Meanwhile, purification is defined as an effort to purify values in culture by reflecting the values of monotheism. The scholars and proponents of Islam in the early era of the existence of Islam in the archipelago realized that the successful delivery of Islam to society had to be peaceful, and to avoid conflict between culture and religion, religious advocates used a culture that society understood and possessed, so that religious and cultural confrontations were avoided. and even complement each other so that acculturation occurs. In Islam there is culture, and in culture there are religious values, and all of them are practiced by humans. Islam membutuhkan kebudayaan dalam rangka penyebaran misi-misinya, baik yang berupa adat, tradisi, seni dan sebagainya. Namun perlu dibedakan mana Islam sebagai agama tauhid yang bersifat universal, absolut dan abadi dan mana yang bersifat relatif, dan temporal sebagai bagian dari kreasi manusia dan sekaligus sebagai ekspresi keislaman.Dakwah kultural tidak lain adalah upaya melakukan dinamisasi dan purifikasi. Dinamisasi bermakna sebagai kreasi budaya yang memiliki kecendrungan untuk selalu berkembang dan berubah ke arah yang lebih baik dan islami. Sedangkan purifikasi diartikan sebagai usaha pemurnian nilai-nilai dalam budaya dengan mencerminkan nilai-nilai tauhid. Para ulama dan penganjur Islam di awal-awal era keberadaan Islam di nusantara menyadari bahwa, kesuksesan penyampaian Islam ke masyarakat haruslah damai, dan untuk menghindari pertentangan budaya dengan agama, para penganjur agama menggunakan budaya yang masyarakat pahami dan miliki, sehingga komprontasi agama dan budaya terhindari dan malah saling melengkapi sehingga terjadi akulturasi. Dalam Islam ada budaya, dan dalam budaya ada nilai-nilai agama, dan semuanya dilakoni oleh manusia.